Seed Germination Biology and Frugivory of an Endemic and Endangered Wild Nutmeg – Myristica magnifica Bedd. (Myristicaceae) - Kamble, Mayur Yashwant; Dalavi, Jagdish Vishnu; Thakur, Rahul Ramesh; Mondal, Anubhab; Bhagure, Pooja Shivaji (Journal of the Bombay Natural History Society (JBNHS), 2025)
Myristica magnifica Bedd. is an endemic and endangered species commonly known as ‘Wild Nutmeg.’ It grows in specific habitats called ‘Myristica swamps,’ a type of relic ecosystem. This study examines the seed germination biology of M. magnifica with detailed illustrations, providing valuable insights for physiologists, forest researchers, and conservationists in multidisciplinary studies, conservation efforts, and species restoration.